2007
DOI: 10.1038/sj.onc.1210452
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress pathways highlighted in tumor cell immortalization: association with breast cancer outcome

Abstract: An improved understanding of cell immortalization and its manifestation in clinical tumors could facilitate novel therapeutic approaches. However, only rare tumor cells, which maintain telomerase expression in vitro, immortalize spontaneously. By expression-profiling analyses of limited-life primary breast tumor cultures pre-and posthTERT transduction, and spontaneously immortalized breast cancer cell lines, we identified a common signature characteristic of tumor cell immortalization. A predominant feature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
(34 reference statements)
1
30
0
Order By: Relevance
“…This is likely due to the fact that gene expression profiles were compared here between cell cultures of equivalent growth rate. A similar observation was made in the identification of a cancer cell immortalization signature based on the comparison of finite life (but proliferating) and immortalized primary breast tumor cells (20). Thus, the association of CPRP-BPA with breast cancer aggressiveness does not merely reflect a correlation between proliferating cells in vitro and those in highgrade tumors.…”
Section: Resultsmentioning
confidence: 77%
“…This is likely due to the fact that gene expression profiles were compared here between cell cultures of equivalent growth rate. A similar observation was made in the identification of a cancer cell immortalization signature based on the comparison of finite life (but proliferating) and immortalized primary breast tumor cells (20). Thus, the association of CPRP-BPA with breast cancer aggressiveness does not merely reflect a correlation between proliferating cells in vitro and those in highgrade tumors.…”
Section: Resultsmentioning
confidence: 77%
“…But does telomerase play a reverse role and modulate oxidative stress? Evidence does seem to point in that direction as several recent studies reported improved response against oxidative stress in hTERT expressing cells (Armstrong et al, 2005;Beliveau and Yaswen, 2007;Dairkee et al, 2007;Lee et al, 2005;Lorenz et al, 2001;Mondello et al, 2006). A recent study with telomerase expressing MRC-5 lung fibroblasts demonstrated a significant translocation of hTERT to the mitochondria following oxidative stress, which was followed by lower mitochondrial DNA damage, reduced mitochondrial peroxide levels and an increase in mitochondrial membrane potential (Ahmed et al, 2008).…”
Section: Effects Of Htert On Oxidative Stressmentioning
confidence: 90%
“…Despite convincing evidence that cellular redox status impacts hTERT biology, the effect of hTERT on cancer cell redox milieu remains less well defined. In this regard, studies have suggested a protective cellular response against oxidative stress in hTERT overexpressing cells (13)(14)(15). In addition, reports have also suggested that hTERT expression positively impacts mitochondrial function by improving its calcium buffering capacity and reducing O 2 À production (16).…”
Section: Introductionmentioning
confidence: 99%